Procedure related complications of fetal blood sampling and in-utero transfusion. (7th June 2011) - Prior, T; Johnstone-Ayliffe, C; Ong, C; Regan, F; Kumar, S
Abstract : In utero transfusion (IUT) was first performed by Liley in 1963. Since then the procedure has become a recognised treatment of both fetal anaemia and thrombocytopaenia. Initially, transfusions were performed via an intraperitoneal route, but with advancing ultrasonographic technology, intravascular IUT became possible, being first performed by Rodeck in 1981. 30 years on from this, the safest, most efficacious technique for IUT has not been established. We report a retrospective observational study of 114 cases of IUT for treatment of fetal anaemia or thrombocytopaenia, at a tertiary referral fetal medicine centre over a 7 year period. Cases were identified from the departments fetal medicine database and patient notes and electronic records retrieved. Pregnancy outcome data was collated from obstetric and neonatal discharge summaries. Despite routine Anti-D prophylaxis, Anti-D alloimmunisation remains the most common cause of fetal anaemia. An MCA PSV of 1.5 MoM was used as indication for FBS, and IUT undertaken at gestations from 17 to 35 weeks. We found transfusions via the Internal Hepatic Vein (IHV) were associated with a lower rate of failure (5%) than those via the primary cord insertion (15%) or cord vein (free loop) (17%). Three cases of in utero death occurred, all in fetuses transfused via the cord vein. Few complications were recorded, the most common being fetal bradycardia during the procedure (8/114). While direct procedural related complications with IUT are rare, the IHV appears to be the most reliable route for IUT, and may be associated with reduced fetal loss rate.